The Nurses’ Innovative Behavior Inventory (NIBI): A development and validation study - Elham Shahidi Delshad; Mohsen Soleimani; Armin Zareiyan; Ali Asghar Ghods (PLoS ONE, 2025)
Introduction Innovative behavior is essential in nurses, driving continuous improvement and operational efficiency, significantly enhancing patient outcomes and overall healthcare quality. This study aims to evaluate the psychometric properties of a specific, theory-driven inventory for measuring nurses’ innovative behavior in Iran. Materials and methods A methodological study was conducted from November 2022 to April 2024. The conceptualization phase involved a qualitative study and a comprehensive literature review to define the concept of nurses’ innovative behavior and identify its key dimensions. The subsequent psychometric evaluation assessed face validity, content validity, construct validity, and structural validity (using exploratory and confirmatory factor analyses) on a sample of 572 clinical nurses. Reliability was evaluated through internal consistency and the test-retest methods. Additionally, responsiveness and interpretability were examined according to the COSMIN checklist. Results The construct validity of a five-factor structure (nurses’ competencies, idea validation, clinical idea implementation, promoting innovation, and generating care ideas), identified during the conceptualization phase, was confirmed. Confirmatory factor analysis yielded a χ2/df ratio of 1.88 for the NIBI five-factor structure. The goodness of fit indices indicated suitable values (CFI = 0.916, AGFI = 0.817, IFI = 0.917, PCFI = 0.709, and RMSEA = 0.057), with all factor loadings greater than 0.5 and statistically significant. Both convergent and divergent validities were demonstrated. The Cronbach’s alpha and omega coefficients ranged from 0.74 to 0.88 and 0.75 to 0.88, respectively. Additionally, the ICC for the entire inventory was 0.975 (CI 0.95–0.98, P < 0.001). Conclusion The findings revealed that the Nurses’ Innovative Behavior Inventory (NIBI) is both valid and reliable, making it a suitable tool for assessing and evaluating innovative behavior in nurses.